Architecture and modern literature (2012)
This is a book about the interpretation of architectural forms in modern literature. One of its claims is that literature’s encounter with the built environment is essential to its de‹nition of what is sometimes called modernity, meaning the set of material and symbolic forms that constitute the modern world and our experience of that world. In order to address this subject, I have found it necessary to pose certain larger questions of the relation between literature and architecture. The introduction puts forward the general question of how meaning is produced by architecture and literature, respectively, and how these meanings have intersected. This question is initially addressed in historical terms, ranging from what I choose to call the foundational myths of Babel and the house of Odysseus to the “house ideologies” of the early modern period. The attention then shifts to the crisis of meaning common to both arts in the nineteenth and twentieth centuries. This crisis manifests itself in a number of ways: in the aesthetics of ruin and fragmentation, in the retreat toward interiority as a space of subjective and private meaning, in the new kinds of attention given to the human body, in the development of new forms and materials, and in the conception of the past in terms of stock or reserve.